Organotellurium-mediated living radical polymerization under photoirradiation by a low-intensity light-emitting diode - Nakamura, Yasuyuki; Yamago, Shigeru (Beilstein Journal of Organic Chemistry, 2013)
A low-intensity (6 W) light-emitting diode (LED) effectively activated an organotellurium chain transfer agent and the dormant species, promoting well-controlled radical polymerization. The use of the LED provided many advantages over the previously reported high-intensity Hg lamp, including high energy efficiency during the polymerization, and easy availability of the low-cost light source. Structurally well-defined poly(methyl methacrylate), poly(methyl acrylate), and polystyrene, with narrow molecular weight distributions, were synthesized under LED irradiation with or without a neutral density filter.
Keywords: free radical; light-emitting diode; living radical polymerization; organotellurium compound; photopolymerization; tellurium; visible light